2018
DOI: 10.1088/1748-9326/aa9e35
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model ensemble projections of European river floods and high flows at 1.5, 2, and 3 degrees global warming

Abstract: Severe river floods often result in huge economic losses and fatalities. Since 1980, almost 1500 such events have been reported in Europe. This study investigates climate change impacts on European floods under 1.5, 2, and 3 K global warming. The impacts are assessed employing a multi-model ensemble containing three hydrologic models (HMs: mHM, Noah-MP, PCR-GLOBWB) forced by five CMIP5 general circulation models (GCMs) under three Representative Concentration Pathways (RCPs 2.6, 6.0, and 8.5). This multi-model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 45 publications
7
126
0
1
Order By: Relevance
“…This is fundamentally different from observational records (which are subject to changing management conditions and transient climate) and transient model simulations. Finally, by combining multiple GCMs with multiple GHMs, the dominant sources of uncertainty in projections (meteorological variability, hydrological response, or model formulation) can be isolated (e.g., Marx et al, 2018;Thober et al, 2017). The design of the large ensembles used here, in combination with the empirical distribution approach, limits the need for (statistical) assumptions, descriptions, and corrections.…”
Section: Discussionmentioning
confidence: 99%
“…This is fundamentally different from observational records (which are subject to changing management conditions and transient climate) and transient model simulations. Finally, by combining multiple GCMs with multiple GHMs, the dominant sources of uncertainty in projections (meteorological variability, hydrological response, or model formulation) can be isolated (e.g., Marx et al, 2018;Thober et al, 2017). The design of the large ensembles used here, in combination with the empirical distribution approach, limits the need for (statistical) assumptions, descriptions, and corrections.…”
Section: Discussionmentioning
confidence: 99%
“…The aim is to provide a consistent framework using a compatible set of standardized forcings and initial conditions for the impact models to investigate low-flow changes under different levels of warming. This multi-model ensemble has recently being used by Thober et al (2017) to analyse projected changes in river floods and high flows in Europe.…”
Section: Methodsmentioning
confidence: 99%
“…The Noah-MP model was originally developed as the land surface component of the 5th generation mesoscale model MM5 to enable climate predictions with physically based ensembles and represents both the terrestrial water and energy cycle (Niu et al, 2011). The PCRaster global water balance model (PCR-GLOBWB) was developed to represent the terrestrial water cycle with a special focus on groundwater and modelling water resources under water stress (Van Beek and Bierkens, 2008;Wanders and Wada, 2015).…”
Section: Climate and Hydrologic Modelsmentioning
confidence: 99%
“…Both DynWat and PCR-GLOBWB 2 use ERA-40 and ERA-Interim forcing Dee et al, 2011;Uppala et al, 2005), with an elevation correction to account for spatial heterogeneity in the elevation (Sutanudjaja et al, 2018), to generate water temperature and runoff estimates for the period 1960-2014. The hydrological input from PCR-GLOBWB 2 has been extensively validated in multiple studies and shown to produce accurate estimates of daily discharge (Sutanudjaja et al, 2018;Van Beek et al, 2011), simulate hydrological extreme events (e.g., He et al, 2017;Marx et al, 2018;Thober et al, 2017;Wada et al, 2013;Wanders & Van Lanen, 2015), and reproduce decadal teleconnections (e.g., Wanders & Wada, 2015b). The river routing in DynWat is similar to that of PCR-GLOBWB and for the discharge simulation performance, we refer to Sutanudjaja et al (2018) for the latest evaluation.…”
Section: Comparing Model Resolutionsmentioning
confidence: 99%